(untitled) (Móin-Móin Magazine - Studies in the Art of Puppetry, 2021)
This article deals with acting women in animation theater during the first fifteen months of the Covid-19 pandemic in Brazil, based on the hypothesis that there is a significant increase in the representation of these actors on the national scene. It presents a brief account of the formation of the Brazilian Puppets Network and some of the main animation theater events held virtually during the period, reflecting on the transformations experienced in the area, due to the reality imposed by the pandemic.